Analysis of the Influence of DER, ROE, PER and EPS on Price Shares in Listed Healthcare Sector Companies on the Indonesia Stock Exchange 2019-2023 - Bela Santia; Mukhzarudfa Mukhzarudfa; Muhammad Ridwan (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the effect of Debt to Equity Ratio (DER), Return On Equity Ratio (ROE), Price Earning Ratio (PER), Earning Per Share (EPS) on Health Sector Companies listed on the Indonesia Stock Exchange in 2020-2023. The population in this study were all health sector companies listed on the IDX. The number of samples collected was 17 companies with 5 years of observation (85 observation data) that met the criteria. The analysis method used was the classical assumption test, multiple linear regression analysis, while hypothesis testing used Simultaneous and Partial tests. The results of this study indicate that DER has a positive and significant to stock prices, ROE is not affects stock prices, PER does not influence on stock prices, EPS has a positive and significant influence on stock prices.